Dampak Media Sosial dan Pornografi Terhadap Perilaku Seks Bebas Anak Di Bawah Umur - Shofiyah Shofiyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Social media is a collection of online communication channels that are dedicated as a means of connecting anyone, including children, anywhere and anytime, for example sharing content, input, community interaction and collaboration, etc. so that social media can change life patterns. someone in the near future with various impacts both positive and negative. The presence of social media through internet networks has contributed greatly to the spread of pornography, because social media has offered diversity and freedom of access to information for its users without having to be bound by restrictions and censorship, so that not a few children are victims of negative viewing (pornography). which was finally copied without thinking about its repercussions. This is evidenced by the rampant free sex behavior among them.